The Role of Emotional Intelligence in Making Successful Financial Decisions - BYKOVA, Svitlana; ZHYLIN, Mykhailo; BULAVINA, Olena; ARTEMCHUK, Mykyta; PURHANI, Safar Hasan (Theoretical and Practical Research in Economic Fields; Vol 15 No 1 (2024): TPREF, Volume XV, Issue 1(29), Spring 2024, 2024)
Emotional intelligence (EI) as the ability for self-analysis, self-motivation, and self-regulation is necessary in the process of financial activity. It ensures informed decision-making, considering consequences and perspectives. The aim is to identify the influence of emotional intelligence on the effectiveness of decision-making by financiers. The following tests were used: EQ (Emotional/Empathy Quotient) test, Melbourne Decision Making Questionnaire, the Rathus Assertiveness Schedule, the Schubert Risk Propensity Test. Statistical processing of the results included the use of descriptive analysis, ANOVA, and regression analysis. The study found that financial workers with a high level of emotional intelligence have a pronounced “vigilance” decision-making style (F=113.4, p≤0.01), high assertiveness (F=103.3, p≤0.01), and risk propensity (F=137.3, p≤0.01). It was proved that emotional intelligence explains the “vigilance” decision-making style (β=0.943, R²=0.572), risk propensity (β=0.896, R²=0.424) and explains 48% of assertiveness (β=0.945, R²=0.483). It was confirmed that emotional intelligence is a predictor of successful financial decisions, it determines high assertiveness, vigilance, and risk propensity. Such results are useful for the development of training and retraining programmes for financiers. At the same time, including the development of assertiveness and risk propensity in professional and corporate training in parallel with the development of EI will give greater chances for the success of financial decisions. The obtained results are important for the financial and economic sphere, as they prove the effectiveness of EI in decision-making. This contributes to the improvement of the system of training competitive financiers and allows to expand aspects of the study of financial success.